2023
DOI: 10.7554/elife.83768
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma-enriched transcripts paradoxically generate osteosarcoma-suppressing extracellular proteins

Abstract: Osteosarcoma (OS) is the common primary bone cancer that affects mostly children and young adults. To augment the standard-of-care chemotherapy, we examined the possibility of protein-based therapy using mesenchymal stem cells (MSCs)-derived proteomes and OS-elevated proteins. While a conditioned medium (CM), collected from MSCs, did not present tumor-suppressing ability, the activation of PKA converted MSCs into induced tumor-suppressing cells (iTSCs). In a mouse model, the direct and hydrogel-assisted admini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Notably, these levels experienced a further elevation in response to the overexpression of VCL (Figure 8 B). It is noteworthy that the tumor-suppressive properties of these proteins have been reported in our earlier studies 15 - 17 . In line with these observations, both the administration of MSC CM induced by LIV and the CM overexpressing VCL led to the downregulation of Amyloid precursor protein (APP), phosphorylated Src (p-Src), and Snail in TT2 cells.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Notably, these levels experienced a further elevation in response to the overexpression of VCL (Figure 8 B). It is noteworthy that the tumor-suppressive properties of these proteins have been reported in our earlier studies 15 - 17 . In line with these observations, both the administration of MSC CM induced by LIV and the CM overexpressing VCL led to the downregulation of Amyloid precursor protein (APP), phosphorylated Src (p-Src), and Snail in TT2 cells.…”
Section: Resultssupporting
confidence: 65%
“…This study revealed heightened ALDOA, PCOLCE, H4, and PPIB levels in MSC CM subjected to LIV treatment. Notably, among these transcripts, PCOLCE and H4 are tumorigenic and substantially expressed in OS, as demonstrated by Kexin et al 17 . PCOLCE, investigated by these researchers, emerged as an extracellular tumor suppressor protein.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations